2023
DOI: 10.3389/fenvs.2022.1013875
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the 2021 East Asia super dust storm using FLEXPART and FLEXDUST and its comparison with reanalyses and observations

Abstract: The 2021 East Asia sandstorm began from the Eastern Gobi desert steppe in Mongolia on March 14, and later spread to northern China and the Korean Peninsula. It was the biggest sandstorm to hit China in a decade, causing severe air pollution and a significant threat to human health. Capturing and predicting such extreme events is critical for society. The Lagrangian particle dispersion model FLEXPART and the associated dust emission model FLEXDUST have been recently developed and applied to simulate global dust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…As the FLEXPART output consists of 3D fields of emission sensitivities, we took the emission sensitivity of the lowest 100 m and coupled it with dust emission fluxes from a FLEXDUST dust emission model (Groot Zwaaftink et al., 2017). We used a version of FLEXDUST that contains several changes to better represent the East Asian dust cycle (Tang et al., 2023). By coupling the dust flux with the emission sensitivity, we obtained source contribution maps, which can be spatially integrated to give the dust deposition rate at the site.…”
Section: Methodsmentioning
confidence: 99%
“…As the FLEXPART output consists of 3D fields of emission sensitivities, we took the emission sensitivity of the lowest 100 m and coupled it with dust emission fluxes from a FLEXDUST dust emission model (Groot Zwaaftink et al., 2017). We used a version of FLEXDUST that contains several changes to better represent the East Asian dust cycle (Tang et al., 2023). By coupling the dust flux with the emission sensitivity, we obtained source contribution maps, which can be spatially integrated to give the dust deposition rate at the site.…”
Section: Methodsmentioning
confidence: 99%
“…The dust emitted in FLEXDUST is assumed to have a volume size distribution between 0.2 and 20 µm according to the brittle fragmentation theory described in . Tang et al (2023) identified several weaknesses in the way dust-emitting areas in East Asia were represented in the original FLEXDUST version. Therefore, we use the updated version of FLEX-DUST by Tang et al (2023), which includes several changes to better represent present day dust emission areas in East Asia.…”
Section: Flexdust and Flexpartmentioning
confidence: 99%
“…Tang et al (2023) identified several weaknesses in the way dust-emitting areas in East Asia were represented in the original FLEXDUST version. Therefore, we use the updated version of FLEX-DUST by Tang et al (2023), which includes several changes to better represent present day dust emission areas in East Asia. To avoid confusion with the standard version of FLEXDUST, we refer to the updated Tang et al (2023) version of FLEXDUST as FLEXDUST-EA.…”
Section: Flexdust and Flexpartmentioning
confidence: 99%
See 2 more Smart Citations